Learning styles in relation to academic performance in virtual modality of students of careers in the health area - Astudillo-Araya, Ángela (2024)
Introduction: The COVID-19 pandemic has forced the adaptation of pedagogical processes, arising the necessity of adapt learning-teaching strategies. Objective: Identify the learning styles among the health area students of Bío-Bío University for virtual education in the COVID-19 pandemic context. Method: Through a stratified random sampling 409 students from the Nutrition and Dietetic, Nursing and Phonoaudiology career. The instrument used for determining the students learning style was “CHAEA-32”. Additionally, a questionnaire was applied for the sociodemographic characterization. Results: The most frequent learning style among students was the Reflector (37.7%), followed by the Theorist (24.4%), the Activist (16.4%), Pragmatist (11.7%), and the Undefined (9.8%). There is no significant relation between learning styles, the variables “academic performance” and “sex”, but with the “present year career”, there is only a significant relation with the theorist and reflector style. Discussion: It is rewarding that the most frequent learning style be the reflector, as it is observed in face-to-face classes, the students show to be analytical, careful, watchful, in relation with the health area student profile. The results suggest the replicability in virtual context of some strategies used in face-to-face classes.